PIPER BETLE EXTRACT PATCH (Piper betle L): THE INFLUENCE IN ADDING REALESE ENHANCER SUBSTANCES TOWARDS PHYSIOCHEMICAL AND ANTIBACTERIAL ACTIVITY - Mufrod Mufrod; Suwaldi Suwaldi; Subagus Wahyuono (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Piper betle extract has an antibactery activity with eugenol as a major active substance its sparingly soluble in water. Piper betle extract mucoadhesive patch was a suitable form used in oral cavity for inhibiting Streptococcus mutans a bactery that caused plaque. Physicochemical properties and the release of active substance affect the acceptability of patch as well as antibacterial activity. Glycerin, propilen glycol and tween 80 are the substances(release enhancer substances/RES) that affect the flexibilty and release the active substance from patc. The aim of the research was to investigate the influance of the concentration of extract and addition of RES to the physicochemical and antibacterial activity of the patchs. Extract obtained by infusion method. Extract piper betle made based on variation concentration of extract 0,5%, 1%,2%,3% ,4% and adding release enhancer subtances glycerin, propilen glycol and tween 80. Patches produced tested for physicochemical properties including uniformity of weight, surface pH, folding endurance, swelling index and antibactery activity. Data obtained were descriptiv and statisticaly analize. The result showed that release enhancer substances affect the physicochemical properties and antibactery activity of the patches. The adding release enhancer substances increasing the value of folding endurance and swelling index and antibactery activity of patch.